Methylene blue therapy in addition to standard treatment for acute-phase septic shock: a pilot randomized controlled trial - Luis-Silva, Fabio; Menegueti, Mayra Gonçalves; Peres, Leandro Moreira; Sepeda, Corina dos Reis; Jordani, Maria Cecília; Mestriner, Fabiola; Petroski-Moraes, Bruno Cesar; Brito-de-Sousa, Joaquim Pedro; Costa-Rocha, Ismael Artur; Cruz, Bruna Lemos; Donadel, Mariana Dermínio; de Souza, Felipe Barizza; et al. (Frontiers in Medicine, 2024)
Purpose: Methylene blue (MB) has been used to increase blood pressure in patients with septic shock by acting on guanylate cyclase and nitric oxide synthase. Objective: To determine whether the administration of MB to patients in the initial phase of septic shock leads to a reduction in the use of vasopressors compared to the Control group. Methods:This was a 1:1 randomized clinical trial of two groups (MB and Control). Forty-two patients were included in the present study; 23 patients were allocated to the Control group, and 19 were randomized to the MB group. Both groups had access to standard treatment, consisting of fluid replacement, vasopressors, and antibiotic therapy. Patients received a loading dose of MB (3 mg/kg) and maintenance (0.5 mg/kg/h) for 48 hours.Vasopressor doses, laboratory test results, inflammatory and anti-inflammatory cytokine levels, and hemodynamic monitoring were recorded before the infusion of MB (T1) and after 20 minutes (T2), 2 hours (T3), 24 hours (T4), 48 hours after the infusion started (T5) and 24 hours after weaning (T6). Results: MB therapy was started together with the indication of vasopressin (VAS) as a second vasopressor. The MB group showed an immediate reduction in NOR dosage, an earlier reduction in VAS dosage, and higher IL-10 levels compared to the Control group. Conclusion: Early administration of MB in combination with standard treatment for septic shock might be reduce vasopressors dose.Continuous infusion of MB for 48 hours was considered safe and there was no adverse events. These results highlight the potential of MB as a safe adjuvant therapeutic option in the treatment of septic shock.Trial registration: Clinical registration: https://ensaiosclinicos.gov.br/rg/RBR-96584w4.